MR Imaging of the Posterior Hypophysis in Children - Gudinchet, F.; Brunelle, F.; Barth, M. O.; Taviere, V.; Brauner, R.; Rappaport, R.; Lallemand, D. (American Journal of Neuroradiology, 1989)
The posterior lobe of the pituitary gland was studied by MR imaging in 30 children without pituitary gland disease and compared with studies from a group of 13 children with central diabetes insipidus, including eight cases of primary diabetes insipidus and five cases of diabetes insipidus secondary to suprasellar tumors (four proved germinomas, one still unknown tumor). Two components in the sella turcica were identified in all 30 children without pituitary gland disease, and the posterior lobe was identified as a high-intensity structure on T1-weighted images. In all 13 patients with diabetes insipidus, the normal hyperintense signal of the posterior hypophysis was absent on T1-weighted images. Three patients with suprasellar tumors presented with a progressively enlarging pituitary stalk on follow-up. Our findings show that absence of the normal hyperintense signal of the posterior lobe is closely related to a loss of function of the neurohypophysis. Size or signal modification of the pituitary stalk should suggest the development of a suprasellar tumor.